NILAI-NILAI MULTIKULTURAL DALAM PEMBELAJARAN SEJARAH: IDENTIFIKASI PADA SILABUS - Uun Lionar; Agus Mulyana (Indonesian Journal of Social Science Education (IJSSE), 2019)
Multicultural Values in History Learning: Identification in Sylabus. Presenting multicultural education in the Indonesian education curriculum is an effort to maintain national integration through education. The education curriculum is basically the realization of people's aspirations about the direction of education. The development of education curriculum must be based on the sociocultural context of society, or according to Brady & Kennedy in Curriculum Construction that the curriculum must fulfill all the interests of society regarding cultural, economic and political development. History learning has a big role in the development of multicultural education, considering the historical history presents various historical facts of the nation which certainly has a diversity of identities and cultures. Through the identification of historical material contained in the syllabus of historical subjects in schools, some content was loaded with the development of multicultural values.